Attached Growth of Sphaerotilus natans in Continuous-Flow Apparatus and Its Growth Inhibition by 9-β-d-Arabinofuranosyladenine - Yoshikawa, Hiroji (1979)
Sphaerotilus natans grew at the maximum specific growth rate (μ(max)) of 0.43/h when cultivated on PGY medium at 25°C. The organism mainly grew attached to inside of the culture vessels when the culture medium was fed to the completely mixed continuous-flow apparatus at a dilution rate above μ(max) and the attached growth was directly related to the dilution rate. When a low concentration of the medium was supplied to the apparatus, almost all of the cells grown were filamentous and attached to the inside of the vessels. When a high concentration of the medium was fed, the organism grew as single cells or short chains and flowed out into the effluent. The attached growth of S. natans in the continuous-flow apparatus was inhibited by the minimal inhibitory concentration of 0.5 to 1.0 μg of 9-β-d-arabinofuranosyladenine per ml. 9-β-d-Arabinofuranosyladenine showed bacteriocidal activity against S. natans at a concentration of 50 to 100 μg/ml.